'If we don't have consent, we need to have beneficence': Requiring beneficence in nonconsensual neurocorrection. (19th May 2022) - Dore‐Horgan, Emma
Abstract: Neurointerventions—interventions that cause direct physical, chemical or biological effects on the brain—are sometimes administered to criminal offenders for the purpose of reducing their recidivism risk and promoting their rehabilitation more generally. Ethical debate on this practice (henceforth called 'neurocorrection') has focused on the issue of consent, with some authors defending a consent requirement in neurocorrection and others rejecting this. In this paper, I align with the view that consent might not always be necessary for permissible neurocorrective use, but introduce a qualification I argue ought to inform our ethical and legal analysis of neurocorrection if we are to administer neurocorrectives nonconsensually. I maintain our use of nonconsensual neurocorrection should be constrained by a beneficence requirement—that it should be limited to neurocorrectives that can be expected to benefit those required to undergo them; and my argument is that a beneficence requirement is necessary in order to safeguard against offender abuse. I highlight how we afford a heightened protective role to beneficence in other instances of biomedical intervention where consent is absent or in doubt; and I argue a beneficence requirement is also necessary in the correctional context because alternative candidate protections would provide insufficiently strong safeguards on their own. I then consider whether requiring beneficence in nonconsensual neurocorrection would (a) be incompatible with penal theory, (b) be objectionably paternalistic, or (c) foreclose many fruitful avenues of crime control. I argue in each case that it would not.